(untitled) (Ibrahim Medical College Journal, 2009)
This study was conducted in 4 selected garment factories within Dhaka city. The objectives of this study were to find out health care access (Supply-side effect) in the garments factory for the women workers and their relation to the productivity. A total of 300 women garment workers were included in this study. Most (60.0%) of the respondents were adolescents, unmarried and having only primary level education (5 years of school education). Their average take home monthly salary was 1791.7 taka which was spent mostly on food. They passed a tight work schedule from 6 AM to 11.30 PM without any rest. Hundred percent of female workers had no previous idea about garments nor had any formal training, but they produced on an average 1016 garment pieces a day. They did not get any vaccine, health education or health related knowledge from the garments factory. There was no provision of health care centre or doctor, treatment for fire burn (other than gas), medicine and support in chronic, severe illness for themselves or their family members. More than half (63.0%) of the respondents mentioned about loss of time due to illness. There was a strong correlation (r=0.858) between sickness and production loss, between hour loss and production loss (r=0.9283), between production loss and percentage loss (r=0.871). Though there was loss due to illness, no health access or facility for women workers in the garments factory was available. To overcome the situation and improve the productivity, owners have to provide health access and women workers have to come forward for their rights. Ibrahim Med. Coll. J. 2008; 2(1): 4-8 Key words: health care, supply-side effect, access, productivity. doi: 10.3329/imcj.v2i1.2923